2008
DOI: 10.1111/j.1743-6109.2008.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ischemic Penile Gangrene: Prompt Partial Penectomy and Other Treatment Options

Abstract: Introduction Penile gangrene is a rare but troublesome problem with high mortality rates. The etiologies could be infectious, traumatic, or vasculogenic. The treatment algorithm is controversial because of limited case numbers. Aim To describe our experiences in treating the patients with ischemic penile gangrene, to review the related literatures, and to try to summarize a practical algorithm for penile gangrene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
0
20
0
5
Order By: Relevance
“…So, early partial penectomy and treatment of underlying conditions can prevent infection and will retain more length of the penis and improve the quality of life. 4 Several authors have reported that the alleged preoperative extension of gangrene is often underestimated compared to intraoperative findings. 4 Even though no signs of secondary infection were observed and the gangrene seemed to be localized on the glans penis in our case, we opted for partial penectomy as our patient was young.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So, early partial penectomy and treatment of underlying conditions can prevent infection and will retain more length of the penis and improve the quality of life. 4 Several authors have reported that the alleged preoperative extension of gangrene is often underestimated compared to intraoperative findings. 4 Even though no signs of secondary infection were observed and the gangrene seemed to be localized on the glans penis in our case, we opted for partial penectomy as our patient was young.…”
Section: Discussionmentioning
confidence: 99%
“…1 Dry gangrene often originates from ischemia 3 or a venoocclusive disease. 4 It is often secondary to diabetes or endstage renal disease leading to secondary hyperparathyroidism. This situation will lead to calciphylaxis of the penile arteries and thus a reduced blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations